2010
DOI: 10.1093/carcin/bgq024
|View full text |Cite
|
Sign up to set email alerts
|

TMPRSS4 induces invasion and epithelial-mesenchymal transition through upregulation of integrin  5 and its signaling pathways

Abstract: TMPRSS4 is a novel type II transmembrane serine protease that is highly expressed on the cell surface in pancreatic, thyroid and other cancer tissues, although its oncogenic significance and molecular mechanisms are unknown. Previously, we have shown that TMPRSS4 promotes invasion, migration and metastasis of human tumor cells by facilitating an epithelial-mesenchymal transition (EMT). In this study, we explored the molecular basis underlying TMPRSS4-mediated effects. We show that multiple downstream signaling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
83
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(88 citation statements)
references
References 34 publications
5
83
0
Order By: Relevance
“…Consistent with the function of E-cadherin as a breast cancer invasion suppressor, experimental knockdown of E-cadherin is sufficient to confer metastatic ability (174). Conversely, exogenous E-cadherin inhibits the migration and extracellular matrix (ECM) invasion of metastatic breast cancer cells, although E-cadherin expression by itself is insufficient to completely reverse the mesenchymal phenotype (177)(178)(179). The consequences of E-cadherin loss for EMT are far reaching and reflect its dual roles in cell adhesion and signalling.…”
Section: Epithelial To Mesenchymal Transitionmentioning
confidence: 83%
“…Consistent with the function of E-cadherin as a breast cancer invasion suppressor, experimental knockdown of E-cadherin is sufficient to confer metastatic ability (174). Conversely, exogenous E-cadherin inhibits the migration and extracellular matrix (ECM) invasion of metastatic breast cancer cells, although E-cadherin expression by itself is insufficient to completely reverse the mesenchymal phenotype (177)(178)(179). The consequences of E-cadherin loss for EMT are far reaching and reflect its dual roles in cell adhesion and signalling.…”
Section: Epithelial To Mesenchymal Transitionmentioning
confidence: 83%
“…This indicates that some prostanoids derived from COXs suppress ovarian tumor growth and that specific inhibition of EP receptor-mediated cell signaling is a valid therapeutic strategy for peritoneal metastasis of ovarian cancer. TMPRSS4 promotes tumor growth, invasion, metastasis, and epithelialmesenchymal transition (15,34). Considering the function of TMPRSS4 in cancer cells, our data showing inhibition of cancer cell growth in SKOV/ip-FuEP2/Ex2-based peritoneal metastasis model are reasonable, and the ineffectiveness of AEBSF alone or in combination with meloxicam may be a result of the expression level of TMPRSS4 being insufficient to suppress cancer cell growth.…”
Section: Discussionmentioning
confidence: 59%
“…Setting the cut-off value of fold change as >4.0 and <0.25, respectively, revealed 6 upregulated genes and 8 downregulated genes in the SKOV/ ip-FuEP2/Ex2-derived tumor (Table II). Three upregulated genes encoded enzymes, namely MMP-7 (4.471-fold), TMPRSS4 (4.348-fold) and CYP1B1 (4.000-fold), each of which has previously been shown to be overexpressed in several types of cancer (12)(13)(14)(15)(16). To validate the result of cDNA microarray, MMP-7, TMPRSS4 and CYP1B1 mRNA from tumor tissue was detected by RT-PCR.…”
Section: Effect Of Secretedmentioning
confidence: 99%
“…Jung and colleagues showed that TMPRSS4 promoted invasion, migration and metastasis of human tumor cells by facilitating an epithelial-mesenchymal transition [14]. Subsequebt data show that TMPRSS4 induces invasion and epithelial-mesenchymal transition through upregulation of integrin alpha5 and its signaling pathways [15]. Recent studies indicate that overexpression of TMPRSS4 is significantly associated with reduced overall survival of patients with non-small cell lung cancer and breast cancer and may represent a potential therapeutic target [10][11]16].…”
Section: Discussionmentioning
confidence: 99%